PENGARUH STRATEGI SERVICE CENTER DALAM PENANGANAN KOMPLAIN TERHADAP KEPUASAN TAMU PADA RESINDA HOTEL KARAWANG - Lia Kusdiana Sari; Titik Akiriningsih; Basrawi Yudi Nugroho (Jurnal Pariwisata Indonesia, 2021)
The purpose of this study was to determine the Service Center strategy implemented by the Front Office department in handling complaints from guests at Resinda Hotel Karawan and to determine the effect of Service Center strategies in handling guest complaints on guest satisfaction at Resinda Hotel Karawang. This research method uses observation, interview, and documentation techniques. Population and sample consisted of 20 people including 1 General Manager, 1 Service Center Supervisor, 4 Duty Managers, 1 Service Center Staff and 13 Guests who have stayed overnight. Types of complaints that occur at the Service Center include complaints in writing or indirectly or verbally or directly. Tips for a hotel in carrying out a complaint handling strategy against guests so that guests feel satisfied while staying or using products / services at the hotel. Because hospitality is one of the accommodation facilities that provide lodging services, food and beverage services and other supporting services. This description shows the importance of how a hotel provides the best service for guests so that guests feel satisfied and have a sense of returning to the hotel. From this analysis, it can be seen that the Service Center strategy carried out by Resinda Hotel Karawang already has a set standard